Pengembangan Media Pembelajaran Berbasis Tiktok Pada Mata Pelajaran Informatika Kelas X TKJ Di SMK Negeri 2 Padang - Sagita, Widia; Irsyadunas, Irsyadunas; Alfiriani, Adlia (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
This learning media development research aims to produce learning media products that are valid and practical so that they are suitable for use in informatics learning class X at SMK Negeri 2 Padang. The method used in this research and development (Research and Development). With the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The source of the data in this study was to carry out a feasibility test in the form of validation using a material validation questionnaire carried out by 3 experts namely, 2 class x informatics teachers at SMK Negeri 2 Padang and 1 lecturer from the informatics education study program, 3 media experts namely a lecturer in the informatics education study program. Data analysis was performed using a Likert scale measurement. With 4 answer options (very valid, valid, less valid, invalid). After these measurements, the material validation results were 89%, media expert validation was 91%. From the results of the analysis it can be concluded that the development of TikTok-based learning media is in very valid and practical criteria and can be used in learning activities in class X informatics subjects. TKJ at SMK Negeri 2 Padang.